Suplementação de taurina em dietas para jundiá (Rhamdia quelen) - Martinelli, Suziane Ghedini (2016)
Taurine is an essential amino acid in several physiological processes in the animal body. Its biosynthesis, from methionine and cystine, differs among the different species of fish and is also affected by their presence or not in the ingredients used in the manufacture of animal feed, so supplementation can improve feed efficiency and protect cells against oxidative damage of reactive oxygen species. The objective of this study was to evaluate the supplementation of taurine on performance, metabolic and antioxidant potential parameters in silver catfish (Rhamdia quelen). Three experiments were conducted on UFSM Fish Farming Laboratory: the first two, lasting 54 days, evaluated the productive performance and metabolic parameters of silver catfish (5g) fed with diet based on plant ingredients or fish meal as a source of protein, both being supplemented with taurine (0, 0.5, 1.5 or 2%). In these experiments, the design was completely randomized, with four levels of supplementation with four replications. In the third experiment, which lasted 24 days, it was evaluated the antioxidant potential of taurine in silver catfish (7g) when supplemented with methionine in semipurified diet. In the latter, the design was completely randomized in a factorial 3x4 (three levels of methionine and four taurine). The results obtained in the experiment with the addition of taurine in the diet with fish meal as protein source indicate that supplementation with this amino acid did not improve the growth of the animals compared to the unsupplemented diet. It was also observed that a higher level of taurine (2%) showed a decrease in growth, rates of protein deposition and consumption, and an increase in feed conversion. For the animals fed with plant diets there was no effect of taurine on growth and consumption. However, the addition of 0.5% taurine in the diet yielded higher protein retention, lower catabolism and better feed conversion, compared to treatment with 2% taurine. Metabolic parameters of the animals in both experiments were not affected by medium supplementation representative of taurine in the diet. In the third experiment, the evaluation of the antioxidant taurine and methionine action showed that with level of 1.5 and 2% taurine and 3.5% methionine had lower protein carbonyl formation and increased activity of antioxidant enzyme superoxide dismutase and decreased protein catabolism. Both growth studies showed that juvenile silver catfish did not require taurine supplementation even when fed with diets containing vegetable sources such as protein-based, though the third experiment showed that taurine has antioxidant action, with respect to the methionine level used.